Capacity assessment of a system for metrological traceability on liquid micro flow rate measurement. (July 2016) - Dias, B L; Aquino, M H; Farias, M H; Koiller, J; Gabriel, P C; Aibe, V Y
Abstract: The necessity of standardizing and traceability to SI in micro scale flow has been subject of intense discuss in the metrology community. The Bureau International of Poids et Mesures (BIPM) has encouraged National Metrology Institutes to be prepared to participate, in 2024, of the first Key Comparison event planned in this area. With this aim, the present work describes a standard system based on gravimetric method for fluid delivery and respective quantification, which was developed by the National Institute of Metrology, Quality and Technology (INMETRO) in order to provide traceability for microflow rate measurement. The system performance and capability were evaluated. An important goal of the work is contribute to the establishment and advancement of researches on microfluidic issues in the Institute.